Father communication coaching for children with autism spectrum disorder: A single-subject study. (September 2019) - Flippin, Michelle
Background and aims: Parent-mediated interventions have been shown to be effective for improving communication skills for children with autism spectrum disorder when implemented by mothers. Little is known about the efficacy of autism spectrum disorder communication interventions implemented by fathers. This study investigated the effects of a 12-week coaching program on a father's use of responsive strategies. Targeted responsive strategies included follow-in comments, follow-in directives, responsive physical play, and responsive object play. Collateral measures of changes to child communication skills and parental stress levels were also investigated. Methods: A single subject, multiple baselines across behaviors experiment was conducted with one dyad (i.e. father and child with autism spectrum disorder). Results: Results showed that the participating father was able to quickly learn to use three of the four targeted responsive strategies (i.e. follow-in comments, follow-in directives, responsive physical play). Child's use of single words increased over baseline level and beginning use of multi-word utterances was documented. Pre–post intervention changes in ratings of stress for the participating father and mother were noted across child and parent domains. Conclusions and implications: Findings of this pilot study may have important implications for developing much-needed parent coaching programs to enhance fathers' use of responsive strategies and increase social communication skills for children with autism spectrum disorder.